1976
DOI: 10.1126/science.1246602
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens: Adverse Effects on Reproduction in California Quail

Abstract: Phytoestrogens, largely formononetin and genistein, are produced in the leaves of stunted desert annuals in a dry year. When ingested by California quail, these compounds apparently inhibit reproduction and prevent the production of young that will not have adequate food. In a wet year, forbs grow vigorously and phytoestrogenic substances are largely absent. Quail then breed prolifically and the abundant seed crop carries the enlarged population through the winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(81 citation statements)
references
References 7 publications
3
75
1
2
Order By: Relevance
“…[40,41] Consumption of plant material with abnormal content of phytoestrogens has been shown to decrease fertility in quail. [42] Intake of excess isoflavanoids (phytosterol) during child hood may lead to moderate decrease in male fertility, including reproductive capacity. [43] In an earlier report, we presented evidence on the effect of GA 3 on serum enzyme and biomarkers and on lipids, and blood cell count in male rat.…”
Section: Discussionmentioning
confidence: 99%
“…[40,41] Consumption of plant material with abnormal content of phytoestrogens has been shown to decrease fertility in quail. [42] Intake of excess isoflavanoids (phytosterol) during child hood may lead to moderate decrease in male fertility, including reproductive capacity. [43] In an earlier report, we presented evidence on the effect of GA 3 on serum enzyme and biomarkers and on lipids, and blood cell count in male rat.…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, one study found high levels of phytoestrogens in the leaves of stunted desert annuals in a dry year, leading ultimately to impaired reproduction when ingested by the California quail (Lophortyx californicus). In wet years, these quails bred normally and phytoestrogens were largely absent in these herbs (Leopold et al, 1976). Finally in captured cheetahs, cases of infertility and liver disease were attributed to the consumption of a soy-based diet and the exposure to high levels of isoflavones ( 50 mg/day; Setchell et al, 1987).…”
Section: Soy and Phytoestrogens As Potential Sources Of Endocrinedisrmentioning
confidence: 99%
“…In addition, phytoestrogens could augment or inhibit estrogen negative feedback by binding to ERs in the anterior pituitary or hypothalamus and indirectly alter ovarian steroidogenesis (see below). Natural dietary exposures to phytoestrogens have been associated with cystic ovaries, irregular estrus, and anestrus in cattle (91), and reduced breeding success in California quail (92). Compromised follicular development (91) and reductions in luteal phase plasma progesterone and E 2 , as well as shortened luteal phases, have been reported in cycling ewes whereas increases in estradiol and cortisol have been reported in pregnant ewes (93,94).…”
Section: Ovarian Cyclicitymentioning
confidence: 99%